Ecological differentiation and assembly processes of abundant and rare bacterial subcommunities in karst groundwater - Zhong, Sining; Hou, Bowen; Zhang, Jinzheng; Wang, Yichu; Xu, Xuming; Li, Bin; Ni, Jinren (Frontiers in Microbiology, 2023)
Ecological heath of karst groundwater has been of global concern due to the increasing anthropogenic activities. Bacteria comprising of a few abundant taxa (AT) and plentiful rare taxa (RT) play essential roles in maintaining the ecosystem stability, yet limited information is known about their ecological differentiation and assembly processes in karst groundwater. Based on metabarcoding analysis of 64 groundwater samples from typical karst regions across Southwest China, we revealed the environmental drivers, ecological roles, and assembly mechanisms of total, abundant, and rare bacterial communities. We found relatively high abundance of potential functional groups associated with parasites and pathogens in karst groundwater, which might link to the frequent regional anthropogenic activities. Our study confirmed that AT were dominated by Proteobacteria and Campilobacterota, while Patescibacteria and Chloroflexi were more flourished in RT subcommunity. The node-level topological features of co-occurrence network indicated AT might share similar niches, and played more important roles in maintaining bacterial community stability. RT in karst groundwater were less environmentally constrained, and showed wider environmental thresholds respond to various environmental factors than AT. Deterministic processes, especially homogeneous selection, tended to be more important in community assembly of AT, whereas community assembly of RT was mainly controlled by stochastic processes. This study expanded our knowledge of the karst groundwater microbiome, and was of great significance to the assessment of ecological stability and drinking water safety in karst regions.